PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BPR LPN SUNGAI RUMBAI DHARMASRAYA (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2017)
ABSTRACT This study aims to determine (1) Effect of Leadership Style on the Work Environment at. BPR LPN Sungai Rumbai Dharmasraya; (2) Influence of Leadership Style to Work Discipline at PT. BPR LPN Sungai Rumbai Dharmasraya; (3) Effect of Leadership Style on Employee Performance at PT. BPR LPN Sungai Rumbai Dharmasraya; (4) Effect of Work Environment on Employee Performance at PT. BPR LPN Sungai Rumbai Dharmasraya; (5) Effect of Work Discipline the Employee Performance at PT. BPR LPN Sungai Rumbai Dharmasraya. This research is a descriptive research Associative. The population in this study were all employees of PT. BPR LPN Sungai Rumbai Dharmasraya. The research sample using total sampling technique with a sample size of 30 employees. The instrument used for research in the form of closed questionnaire. The assay used in this study were (1) Inductive analysis, (3) Test Path Analysis, (3) Test the hypothesis.